American Time Use Survey (ATUS), 2011 ([Verlag nicht ermittelbar], 2014)
The American Time Use Survey (ATUS) collects information on how people living in the United States spend their time. Data collected in this study measured the amount of time that people spent doing various activities in 2011, such as paid work, child care, religious activities, volunteering, and socializing. Respondents were interviewed only once about how they spent their time on the previous day, where they were, and whom they were with. Part 1, Activity File, includes additional information on activities in which respondents participated, including the location of each activity and the total time spent on secondary child care. Part 2, Call History File, gives information about each call attempt. Part 3, Case History File, contains information about the interview process. Part 4, ATUS-CPS File, contains demographic and occupational data on respondents and members of their household collected during their participation in the Current Population Survey (CPS). Part 5, Respondent File, contains demographic information about respondents. Part 6, Roster File, contains information about household members and non-household children under the age of 18. Part 7, Eldercare Roster File, file contains information about people for whom ATUS respondents provided care. Part 8, Activity Summary File, contains a summary of the total amount of time they spent doing each activity that day. Part 9, Replicate Weight File, contains miscellaneous ATUS weights. Part 10, Who File, includes codes that indicate who was present during each activity. Part 11, ATUS Leave Module Respondent File, contain information related to wage and salary workers' access to paid and unpaid leave and the ability to adjust their work schedules and locations instead of taking leave or because they didn't have access to leave. Part 12, ATUS Leave Module Replicate Weights File, contains weights for Part 11, ATUS Leave Module Respondent File.